Quantification of Solid Embryonic Cerebellar Graft Volume in a Degenerative Ataxia Model - Purkartova, Zdenka; Krakorova, Kristyna; Babuska, Vaclav; Tuma, Jan; Houdek, Zbyněk; Roy Choudhury, Nilpawan; Kapl, Stepan; Kolinko, Yaroslav; Sucha, Martina; Porras-Garcia, Elena; Kralickova, Milena; Cendelin, Jan (Cerebellum (London, England), 2024)
Substitution of lost neurons by neurotransplantation would be a possible management of advanced degenerative cerebellar ataxias in which insufficient cerebellar reserve remains. In this study, we examined the volume and structure of solid embryonic cerebellar grafts in adult Lurcher mice, a model of olivocerebellar degeneration, and their healthy littermates. Grafts taken from enhanced green fluorescent protein (EGFP)-positive embryos were injected into the cerebellum of host mice. Two or six months later, the brains were examined histologically. The grafts were identified according to the EGFP fluorescence in frozen sections and their volumes were estimated using the Cavalieri principle. For gross histological evaluation, graft-containing slices were processed using Nissl and hematoxylin-eosin staining. Adjustment of the volume estimation approach suggested that it is reasonable to use all sections without sampling, but that calculation of values for up to 20% of lost section using linear interpolation does not constitute substantial error. Mean graft volume was smaller in Lurchers than in healthy mice when examined 6 months after the transplantation. We observed almost no signs of graft destruction. In some cases, compact grafts disorganized the structure of the host's cerebellar cortex. In Lurchers, the grafts had a limited contact with the host's cerebellum. Also, graft size was of greater variability in Lurchers than in healthy mice. The results are in compliance with our previous findings that Lurcher phenotype-associated factors have a negative effect on graft development. These factors can hypothetically include cerebellar morphology, local tissue milieu, or systemic factors such as immune system abnormalities.
Keywords: modely nemocí na zvířatech; Neurotransplantation; Lurcher mice; transplantace mozkové tkáně; Cerebellar Ataxia; Cerebellum; Brain Tissue Transplantation; zelené fluorescenční proteiny; Animals; myši transgenní; zvířata; Disease Models, Animal; Green Fluorescent Proteins; myši; mozeček; cerebelární ataxie; Mice; Olivocerebellar degeneration; Mice, Transgenic